Smallholder cattle farmers' willingness to adopt index-based livestock insurance in the face of climate change : evidence from Polokwane Local Municipality, Limpopo Province - Maekela, Koena Frans (My University, 2022)
Climate change and variability on a global level is one of the most serious environmental challenges which exacerbates the well-known vulnerability of smallholder farmers. To cushion the shock of climate change, risk management plays a crucial role in farming, and in the same context, insurance positions itself as one of the main risk management instruments available to farmers. However, one of the key reasons to the struggles of smallholder farmers in South Africa is the inability to obtain effective insurance. To this end, the study identified and profiled the socio-economic features of smallholder cattle farmers, identified smallholder cattle farmers’ perceptions on components of climate change as sources of risk to cattle production and finally, analysed the determinants of willingness to adopt IBLI among smallholder cattle farmers. A purposive multistage sampling procedure was used to identify 110 smallholder cattle farmers in the Polokwane local Municipality. IBM SPSS version 26 and STATA version 15 was used to analyse the primary cross-sectional data collected through structured questionnaire interviews. Farmers’ perceptions on components of climate change as sources of risk were identified using the Principal Component Analysis (PCA). The PCA revealed three principal components (PCs) explaining almost 61% of the variance of the original variables (climate change components). Furthermore, about 89% of the sampled farmers were willing to adopt IBLI, while about 11% weren’t willing to adopt and the Probit regression model results revealed that marital status, farming experience, access to extension services, off- farm income and land ownership, farmers’ educational level, household size, experience of livestock loss and farm size significantly influenced willingness to adopt IBLI. Based on the findings of this study, the recommended interventions include workshops for raising IBLI awareness, government subsidy on insurance premiums and finally, increased extension service reach to smallholder cattle farmers.
Thesis (M.Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2022
Keywords: Climate change; Smallholder farmers; Index-based insurance; Risk management; Farm ownership; Climatic changes -- South Africa -- Limpopo; Farmers -- South Africa -- Limpopo; Farms, Small -- South Africa -- Limpopo; Agricultural insurance